Comparative Analyses of Phyllosphere Bacterial Communities and Metabolomes in Newly Developed Needles of Cunninghamia lanceolata (Lamb.) Hook. at Four Stages of Stand Growth - Sun, Kun; Sun, Honggang; Qiu, Zonghao; Liu, Qiang (Frontiers in Plant Science, 2021)
Phyllosphere is a vast habitat for microbial communities. Host-plant-associated bacteria affect the growth, vigor, and nutrient availability of the host plant. However, compared with foliar endophytes, phyllosphere bacteria have received less research attention and their functions remain elusive, especially in forest ecosystems. In this study, we collected newly developed needles from sapling (age 5 years), juvenile (15 years), mature (25 years), and overmature (35 years) stands of Chinese fir (Cunninghamia lanceolata(Lamb.) Hook). We analyzed changes in the phyllosphere bacterial communities, their functional genes, and metabolic activity among different stand ages. The phyllosphere bacterial community showed changes both in relative abundance and in composition, with increase in stand age. Community abundance predominantly changed in the orders Campylobacterales, Pseudonocardiales, Deinococcales, Gemmatimonadales, Betaproteobacteriales, Chthoniobacterales, and Propionibacteriales. Functional predictions indicated the genes of microbial communities for carbon metabolism, nitrogen metabolism, antibiotic biosynthesis, flavonoids biosynthesis, and steroid hormone biosynthesis varied. Bacterial abundance was strongly correlated with metabolites. In total, 112 differential metabolites, including lipids, benzenoids, and flavonoids, were identified. Trigonelline, proline, leucine, and phenylalanine concentration increased with stand age. Flavonoids concentrations were higher in sapling stands than in other stands, but the transcript levels of genes associated with flavonoids biosynthesis in newly developed needles of saplings were lower than those of other stands. Nutritional requirements and competition between individual trees at different growth stages shape the phyllosphere bacterial community and host–bacteria interaction. Phyllosphere bacteria provide various secondary metabolites, such as flavonoids, to Chinese fir saplings and thereby promote sapling growth.